2016
DOI: 10.1177/2165079916653767
|View full text |Cite
|
Sign up to set email alerts
|

Association Among Sociodemograhic Factors, Work Ability, Health Behavior, and Mental Health Status for Young People After Prolonged Unemployment

Abstract: The purpose of this study was to explore the associations of prolonged unemployment, health, and work ability among young workers using data from the 2008-2010 Occupational Health Counselling project in Kuopio, Eastern Finland. The total sample for this study was 190 young unemployed adults. The questionnaire included the Work Ability Index (WAI), the Beck Depression Inventory, the Alcohol Use Disorders Identification Test, and the Occupational Health Counselling Survey. Multivariate analyses revealed that men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Work ability was lower among participants who had been unemployed 3 years or over. According to earlier cross-sectional studies, work ability declined when unemployment was prolonged (Hult and Lappalainen 2018;Lappalainen et al 2017;Lundin et al 2016;Szlachta et al 2012) and our findings confirm that. Additionally, Szlachta et al (2012) found that repeated failures in gaining employment, deteriorating well-being, and lowered self-esteem, are associated with a longer period of unemployment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Work ability was lower among participants who had been unemployed 3 years or over. According to earlier cross-sectional studies, work ability declined when unemployment was prolonged (Hult and Lappalainen 2018;Lappalainen et al 2017;Lundin et al 2016;Szlachta et al 2012) and our findings confirm that. Additionally, Szlachta et al (2012) found that repeated failures in gaining employment, deteriorating well-being, and lowered self-esteem, are associated with a longer period of unemployment.…”
Section: Discussionsupporting
confidence: 90%
“…Prolonged unemployment is associated with deteriorating health (e.g. Nurmela et al 2018;Worach-Kardas and Kostrzewski 2014;Butterworth et al 2012;Pharr et al 2012) and work ability (Hult and Lappalainen 2018;Lappalainen et al 2017;Lundin et al 2016;Szlachta et al 2012). The proportions of unemployed persons who perceive themselves as having good work ability (a score of eight or above on a scale of 0-10) vary between 30% and 60% in different studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there has been quite little research on the work ability of unemployed people. It is known, however, that long-term unemployment, being over 45 years of age, and having a low level of education are positively associated with decreased work ability (Lappalainen et al, 2017;Szlachta et al, 2012). There is a need for research that identifies not only the possible causes of decreased work ability, but also the factors that may improve work ability.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Describing the level of different aspects of functioning requires the use of standardized, reliable, and valid instruments. An individual's own perception of their functioning also plays a critical role (Asante et al 2007;Brouwer et al 2010;Hult and Lappalainen 2018;Kevin et al 2008;Lappalainen et al 2017;Szlachta et al 2012;Vastamäki et al 2014).…”
Section: Introductionmentioning
confidence: 99%